MEMAHAMI KONSEP DAN SUBJEK PERTANGGUNGJAWABAN PIDANA DALAM PASAL 39A UNDANG-UNDANG NOMOR 28 TAHUN 2007 TENTANG PERUBAHAN KETIGA UNDANG-UNDANG NOMOR 6 TAHUN 1983 TENTANG KUP: Suatu Pengantar - Yumanto, Bina (Scientax, 2021)
In various cases of tax criminal acts, the board of directors is often subject to criminal liability on the grounds of being a signatory to the Tax Return (and/or Tax Invoice) and as a corporate organ that is deemed responsible for all company policies, activities, and operations. In addition, some cases of Tax Criminal Investigation impose criminal responsibility on the board of directors based on evidence of signature in the Tax Return and consideration of the principle of vicarious liability, which is the expansion or representation of liability for compensation under Private Law. This study aims to analyze the criminal liability doctrine adopted by Article 39A of Law Number 28 of 2007 concerning the Third Amendment to Law Number 6 of 1983 concerning General Provisions and Tax Procedures (UU KUP) and whether corporations can be held criminally liable in the offense of that Article. The theory and concepts used are criminal liability and analysis of the elements of Article 39A of the UU KUP, the main doctrines of criminal liability, the definition of legal entities, corporate taxpayers, and corporate liability. The results of the study found that corporate taxpayers as corporations are the subject of criminal liability in Article 39A, in addition to individuals, and Article 39A adheres to the principle of no crime without guilt.